A Garch Study On Exchange Rate Determinants: A Case Of Malaysia - Mohd Farhan Mohd Ali; Sharifah Fairuz Syed Mohamad; Anis Suraya Mohammad Yusof; Noor Adilah Ibrahim; Shahrina Ismail (Malaysia Institute of Statistics (ISMy) and Centre for Foundation Studies in Science, Universiti Malaya, 2024)
Non-Indexed Publication